NILAI EKONOMI EKOSISTEM TERUMBU KARANG DI PULAU BALIKUKUP KECAMATAN BATU PUTIH KABUPATEN BERAU - Freddy Mariyanto; Erwan Sulistianto; Nurul Ovia Oktawati (2339-1324, 2015)
The purposed of the research is to analized economic value of coral reef ecosystem in Balikukup island based on fishing. Sample was taken with Purposive Sampling method than analyzed with Effect on Productivity (EOP). The results showed that the economic value of coral reef ecosystem in Balikukup island is Rp. 13.100.714/ha/year. It’s mean, if the coral reef ecosystem in Balikukup island demaged, the government disadvantage is Rp.13.100.714/ha/year.